2014
DOI: 10.1364/ol.39.001117
|View full text |Cite
|
Sign up to set email alerts
|

Physical conditions of single-longitudinal-mode operation for high-power all-solid-state lasers

Abstract: The optimal physical conditions of single-longitudinal-mode (SLM) operation for continuous-wave all-solid-state lasers with high output powers are investigated theoretically and experimentally. The dependence of the operation conditions on the linear and nonlinear intracavity losses of the laser is numerically calculated. The theoretical analysis is demonstrated by the experimental measurements on a home-made Nd:YVO4 laser. The stable SLM output up to 33.7 W with optical-optical conversion efficiency of 44.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 13 publications
0
25
0
2
Order By: Relevance
“…The transmission curve of the inset in Fig. 4 confirmed that the 1064 nm laser was stably running in SLM operation, revealing that the introduced nonlinear loss by the nonlinear LBO crystal was large enough to effectively suppress the multi-mode oscillation and mode hopping of the laser [6,8,14]. The long-term power stability of the 1064 nm laser was measured during an 8 h period.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The transmission curve of the inset in Fig. 4 confirmed that the 1064 nm laser was stably running in SLM operation, revealing that the introduced nonlinear loss by the nonlinear LBO crystal was large enough to effectively suppress the multi-mode oscillation and mode hopping of the laser [6,8,14]. The long-term power stability of the 1064 nm laser was measured during an 8 h period.…”
mentioning
confidence: 66%
“…In recent years, a large amount of work has been done to scale up the optical power and improve the beam quality of the single-frequency all-solid-state laser, such as direct pumping technology [4], dual-end pumping scheme, adopting a composite laser crystal [3], employing a low-doped laser crystal with long length, self-compensating the astigmatism of the laser [4], and active compensation of the thermal lens effect with a negatively thermal-optical crystal [5]. In addition, for ensuring the single-longitudinal-mode (SLM) characteristic of the laser with the high output power, a method of introducing a nonlinear loss to a unidirectional resonator was developed [6], where loss difference between the lasing mode and side non-lasing modes can effectively suppress the oscillation of the non-lasing modes [7]. Up to now, a stable single-frequency 1064 nm laser with the highest output power of 50.3 W had been achieved, which was realized by a combination of a direct pumping scheme, composite laser crystal, and astigmatism selfcompensation with the nonlinear loss [8].…”
mentioning
confidence: 99%
“…The free spectrum range and the finesse (f) of the F-P cavity are 750 MHz and 150, respectively. It demonstrates that the laser works with single-frequency operation, which is owing to the existence of the nonlinear loss introduced by the nonlinear crystal [16].…”
Section: Resultsmentioning
confidence: 98%
“…In order to improve the oscillating performance, the nonlinear loss is introduced into the resonator of a single-frequency laser with high gain [22,23] . In that case, the laser can achieve a high output with a single-frequency operation and dichromatic laser beams, and the intensity noises of the FW and SHW can be manipulated by tuning the nonlinear loss [24] .…”
mentioning
confidence: 99%
“…ω 1 and ω 2 are the beam waists of the laser medium and the nonlinear crystal, respectively, dn z dT and dn y dT are the temperature coefficients of the refractive indexes of the FW and SHW in the nonlinear crystal [23,25] , respectively, and ΔT is the temperature mismatch. Equation (5) denotes that the value of η is decided by ΔT when the material and the length l of the nonlinear crystal are chosen.…”
mentioning
confidence: 99%